(untitled) - Proakis, John G. (Australia, 2013)
Contemporary Communication Systems Using MATLAB.' Featuring a variety of applications that motivate learners, this books serves as a companion or supplement to any of the comprehensive textbooks in communications systems.
Keywords: Hệ thống truyền dữ liệu,Data transmission systems; Mô phỏng máy tính,Computer simulation